Estimating the distribution of household wealth in South Africa - Aroop Chatterjee; Léo Czajka; Amory Gethin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper estimates the distribution of personal wealth in South Africa by combining tax microdata, household surveys, and macroeconomic balance sheet statistics. We systematically compare estimates of the wealth distribution obtained by direct measurement of net worth, rescaling of reported wealth to balance sheet totals, and capitalization of income flows. We document major inconsistencies between available data sources, in particular regarding the measurement of dividends, corporate assets, and wealth held through trusts. Both household surveys and tax data remain insufficient to properly capture capital incomes. Notwithstanding a significant degree of uncertainty, our findings reveal unparalleled levels of wealth concentration. The top 10 per cent own 86 per cent of aggregate wealth and the top 0.1 per cent close to onethird. The top 0.01 per cent of the distribution (3,500 individuals) own 15 per cent of household net worth, more than the bottom 90 per cent as a whole. Such high levels of inequality can be accounted for in all forms of assets, including housing, pension funds, and other financial assets. Our series show no sign of decreasing wealth inequality since apartheid; if anything, we find that inequality has remained broadly stable and has even slightly increased within top wealth groups.
Keywords: D31; E01; E21; I31; 330; administrative data; households balance sheets; income capitalization; micro-macro gap; national accounts; wealth distribution; wealth surveys